APPLICATION OF LEARNING CYCLE 5E (LC5E) LEARNING MODEL TO IMPROVE MATHEMATICS LEARNING OUTCOMES SMK RIAU TAXATION - Sri Rizka Putri; Alzaber (UIR PRESS, 2020)
This study aims to improve the learning process and improve mathematics learning outcomes for the Riau Taxation Vocational School students through Learning Cycle 5E (LC5E). This research is classroom action research which consists of 2 cycles. The subjects in this study were students SMK Riau Taxation, totaling 24 people, with 21 female students and three male students. Data collection instruments in observation sheets and learning outcomes tests were collected using observation and test techniques. The data analysis was carried out by analyzing qualitative data for observation sheets and quantitative data for learning outcomes tests. The results showed an increase in student learning outcomes. The number of students who achieved the KKM increased in UH ​​1 and UH 2 from the basic score. The percentage of completeness on the basic score is 45% (11 students) at UH I, is 62.50% (15 students), and at UH 2, 70.83% (17 students). From the results of the research above, it can be concluded that the application of Learning Cycle 5E (LC5E) can improve the learning process and improve student learning outcomes in Mathematics at the Riau Taxation Vocational School, especially in arithmetic sequences and series material